Komunikasi Gethok Tular dan Kemitraan sebagai Kekuatan Branding Ginastel dalam Memberdayakan UMKM - Zeny Indarwati; Joko Suryono; Yoto Widodo; Bono Setyo; Hariyanto Hariyanto (Communications, 2026)
The objectives of this research are 1) Attempt to reveal the strengths, criteria and uniqueness of the Ginastel brand; 2) secondly, what marketing communication patterns are used in establishing partnerships between Ginastel tea management and Ginastel partners, as well as in targeting consumers; 3) Describe community empowerment efforts through partnership patterns carried out by Ginastel tea. This research method uses a qualitative descriptive research type. Research subjects included key informants, main informants and supporting informants consisting of management, partners and consumers of Ginastel tea. The location of this research is in Sukoharjo Regency. Data collection techniques use in-depth interview techniques and direct role observation and listening on social media. Data analysis techniques use Miles and Huberman's interactive inductive logic model. Validity testing uses method triangulation and source triangulation techniques. The results of this research are: 1) The Ginastel tea brand has a unique and prominent strength from the substance of the words Ginastel, legi, hot, sepet, kenthel and the delicious taste of tea that the Javanese people like and enjoy. Ginastel's branding strength is based on local Javanese cultural wisdom; 2) Ginastel tea marketing communication patterns in establishing collaborative partnerships with the community and targeting consumer targets using social media TikTok, Instagram and Gethok tular communication media. The synergy between contemporary marketing communication media and infectious disease communication media is considered interesting because they both strengthen each other; 3) The strength of the Ginastel tea brand is being able to empower the community through a partnership system. The strength of the Ginastel tea brand has developed into a brand that can become a franchise business which has an impact on expansion and job creation.